Redescription of Lasioseius floridensis Berlese, 1916 (Acari: Mesostigmata: Blattisociidae), with notes on closely related species - Britto, Erika P. J.; Lindquist, Evert E.; de Moraes, Gilberto J. (Zootaxa, 2011)
A redescription of Lasioseius floridensis Berlese, 1916 is presented based on examination with descriptive notes of primary type material in the Berlese Collection and on a study of specimens collected from gerbera leaves in Mogi das Cruzes, State of Sao Paulo, Brazil representing all postembryonic stages. This species was originally described from Lake City, Florida, USA, where it was collected from moss; it is considered a senior synonym of Lasioseius arboreus Chant, 1963 (new synonymy) and Lasioseius fimetorum Karg, 1971 (new synonymy), based on examination of primary type material of the latter two species. Examination of other primary type material also indicated that Lasioseius sugawarai Ehara, 1964 is a senior synonym of Lasioseius tridentatus Baker, Delfinado & Abbatiello, 1976 (new synonymy). Placement of L. floridensis among other of the ca 150 species of Lasioseius, based on available keys, and the need for more detailed descriptions of species of genera such as Lasioseius, confirmed by examination of their primary type material, are discussed.